The Genome of a Southern Hemisphere Seagrass Species (Zostera muelleri) . Issue 1 (3rd July 2016) - Lee, HueyTyng; Golicz, Agnieszka A.; Bayer, Philipp E.; Jiao, Yuannian; Tang, Haibao; Paterson, Andrew H.; Sablok, Gaurav; Krishnaraj, Rahul R.; Chan, Chon-Kit Kenneth; Batley, Jacqueline; Kendrick, Gary A.; Larkum, Anthony W.D.; et al.
Abstract : Adaptation of seagrass to the marine environment involves modification and loss of conserved plant genes. Abstract: Seagrasses are marine angiosperms that evolved from land plants but returned to the sea around 140 million years ago during the early evolution of monocotyledonous plants. They successfully adapted to abiotic stresses associated with growth in the marine environment, and today, seagrasses are distributed in coastal waters worldwide. Seagrass meadows are an important oceanic carbon sink and provide food and breeding grounds for diverse marine species. Here, we report the assembly and characterization of the Zostera muelleri genome, a southern hemisphere temperate species. Multiple genes were lost or modified in Z. muelleri compared with terrestrial or floating aquatic plants that are associated with their adaptation to life in the ocean. These include genes for hormone biosynthesis and signaling and cell wall catabolism. There is evidence of whole-genome duplication in Z. muelleri ; however, an ancient pan-commelinid duplication event is absent, highlighting the early divergence of this species from the main monocot lineages.